2004
DOI: 10.1158/0008-5472.can-03-1246
|View full text |Cite
|
Sign up to set email alerts
|

Neural Progenitor Cell Lines Inhibit Rat Tumor Growth in Vivo

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 34 publications
3
61
1
4
Order By: Relevance
“…The abundance of neural precursors at the tumor is associated with reduced tumor size and increased survival as studied in an animal model, and in vitro, precursor cells have a direct antitumorigenic effect. Such antitumorigenic effects have been described previously for exogenously added immortalized neural precursor cells from newborn mice (Benedetti et al, 2000;Staflin et al, 2004), but in those studies, no relationship to endogenous, nonimmortalized precursor cells could be established. Implanted immortalized precursors display tropism for experimental glioblastomas (Aboody et al, 2000).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The abundance of neural precursors at the tumor is associated with reduced tumor size and increased survival as studied in an animal model, and in vitro, precursor cells have a direct antitumorigenic effect. Such antitumorigenic effects have been described previously for exogenously added immortalized neural precursor cells from newborn mice (Benedetti et al, 2000;Staflin et al, 2004), but in those studies, no relationship to endogenous, nonimmortalized precursor cells could be established. Implanted immortalized precursors display tropism for experimental glioblastomas (Aboody et al, 2000).…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, however, the unmodified control cells in that study enhanced survival, too. A recent study confirmed the effects on survival of in vitro expanded neural precursor cell lines administered into gliomas (Staflin et al, 2004). Currently, no gene therapy strategies have been approved for glioblastoma, and clinicians rely on the classic therapies, namely, surgery, chemotherapy, and cranial irradiation (Noble, 2000).…”
Section: Introductionmentioning
confidence: 91%
“…Benedetti and Staflin et al described the ability of nonengineered rat neural progenitors to inhibit glioma growth in vivo. 25,26 The exact mechanism underlying the observations remains unclear, although they have reported that NSCs may elaborate a secretory agent that could inhibit tumor cell growth. For verifying this demonstration, we co-cultured BMSCs and C6 at the ratio of 1:1.…”
Section: Discussionmentioning
confidence: 99%
“…Cultivated NPCs release soluble factors that can attenuate glioblastoma proliferation Staflin et al, 2009;Suzuki et al, 2005), cause glioblastoma cell death Walzlein et al, 2008) and induce the differentiation of glioblastoma stem cells (Chirasani et al, 2010). In mouse glioblastoma models, using orthotopic implantation of glioblastoma cells, it was shown that coimplantation of cultivated NPCs improves survival Staflin et al, 2004). The tumor-suppressing capacity of endogenous NPCs may explain, why glioma growth is attenuated in younger animals and why younger mice outlive older animals after glioblastoma inoculation into the brain.…”
Section: The Interaction Of Glioblastomas With Neural Precursor Cellsmentioning
confidence: 99%